Concept results as a vector of effect / Концепция результанты как вектор эффекта - JELESCU Petru; JELESCU Dumitru (EcoSoEn: Ştiinţe Economice, Sociale şi Inginereşti = Economics, Social and Engineering Sciences)
In this article, on the basis of scientific analysis, synthesis and generalization, the essence of the main psychological concepts of development is considered from a historical point of view. In this context, the resultant theory (our term is R. J., M. T.) is proposed for discussion as a logical continuation of historically previous concepts, which is applicable not only to the human, but also to the non-human world / worlds. Therefore, in our opinion, this theory is universal. The article provides a formula for the mathematical calculus of the resultant (R). Concrete and convincing examples of the use of the resultant theory for the preparation of Olympians in mathematics, in other areas of human life and activity, but not only, for example, in the organic (plant, animal) and inorganic worlds (physical, chemical) are given. I would like to hope that, gradually, this theory will take root, become habitual, and after it new, more advanced ones will appear, contributing to human progress.